Memorandum on the situation in Asturias
011-0036-003 -2- and surest bulwarks against disorder und anarchy. And the importance of this for the future is obvious, since such repressive measures would form one of the greatest obstacles to the moral unification of the Spanish nation as a whole. (3) Endeavours are being made to ensure the first negotiations towards saving the lives of these people by means of the formula accepted by the Spanish Government, which consists in liberating the political prisoners in the hands of the authorities of the Government in Gijon (women and children without reserve; men of military age to be convoyed to and interned in a foreign country;) in exchange for the rebel authorities allowing the transportation of the civilian population by sea. (4) But if this formula were accepted (and it is not certain that it will be) there would still remain the problem of the combatants, and especially of the leaders. In view of the geographical situation of this region, if the resistance of those men should at last be overcome, they would have no alternative but to throw themselves into the sea or surrender; in either case it would mean certain death. In these tragic and exceptional circumstances would it not be possible for France and England to consider the maritime frontier of Asturias as a land frontier? What would happen if these men found themselves facing, not the sea but the French frontier ? They would cross it, and would be disarmed and interned by the French authorities in French territory. Would it not be possible in the same way for those men, should the occasion arise, to embark in French and English ships, their embarkation to be considered as the equivalent of the act of crossing a land frontier ? This would mean notifying the rebels that the French and English fleets would protect these ships not only on the high seas but also within Spanish territorial waters and so far both Governments have refused to do this. But the fact 292/946/11/36(iii)